Zwischen lebensunwertem und selbstbestimmtem Leben. Impulse des 20. Jahrhunderts für eine ableismuskritische Religionspädagogik - Neumann, Anna (Katastrophen. Religiöse Bildung angesichts von Kriegs- und Krisenerfahrungen im 19. und 20. Jahrhundert)

Jesus heilt. Warum nicht alle? Heilungswunder aus der Perspektive von Menschen mit Behinderung - Neumann, Anna; Kammeyer, Katharina (Religion 5-10)

The Importance of Distrust in AI - Peters, Tobias Martin; Visser, Roel W. (Communications in Computer and Information Science)

From European Symbolism to German Gesture: The International and Transnational Nationalism of Stefan George’s Blätter für die Kunst - Gretz, Daniela (German Literature as a Transnational Field of Production, 1848-1919)

Conceptual understanding of third grades for axial symmetry - Wallner, Melina; Häsel-Weide, Uta (International Symposium in Elementary Mathematics Teaching. Proceedings: New Directions in Elementary Mathematics Education)

Employer Branding - Wie Arbeitgeber strategisch gegen den Arbeitskräftemangel vorgehen. - Schneider, Martin; Radermacher, Katharina (Die Politische Meinung)

Transformationen des Faktualen. Darstellungsstrategien multimodalen Erzählens in der biografischen Graphic Novel "Guantanamo Kid. Die wahre Geschichte des Mohamed al Gharani" - Böker, Ines; Willeke, Stephanie (Literatur im Unterricht. Texte der Gegenwartsliteratur für die Schule. Krieg. Repräsentationen in Literatur und Medien der Gegenwartsliteratur.)

(Ver-)störendes Held*innentum. Figurationen und Repräsentationen von Soldatinnen und Soldaten in postheroischen Kriegszeiten - Böker, Ines (Limbus. Australisches Jahrbuch für germanistische Literatur und Kulturwissenschaft)

Nachhaltigkeit in der Bildung fOERdern: Open Educational Resources in der Hochschullehre - Weber, Tassja (Inverted Classroom and beyond 2023: Agile Didaktik für nachhaltige Bildung)

A model of cycles and bubbles under heterogeneous beliefs in financial markets - Burs, Carina (Cogent Economics & Finance)
I study the effect of heterogeneous beliefs about asset prices on the long-term behavior of financial markets. Starting from the ideas of Abreu and Brunnermeier (Citation2003), a two-dimensional system of differential equations is developed. The first dynamic variable is the asset price growth rate. The second dynamic variable is the number of investors who believe that asset prices are abnormally high. In a phase plane analysis, I find both stable and unstable equilibria, depending on the spread of information and the response to other agents’ beliefs. If individuals try to increase their returns while perceiving more overpricing, these equilibria can be spirals or even approach limit cycles. Although I intend to study general price patterns, abnormally high asset prices can be caused by financial bubbles. In this model, bubbles can emerge and deflate both in cycles or directly, or they can grow until they burst. Further, I analyze market behavior after a central bank increases the interest rate. This can lead to new stable equilibria, but the emergence and bursting of bubbles cannot be prevented.
Keywords: asset pricing; subjective information; stability conditions; monetary policy; risk aversion